(untitled) (Anclajes, 2024)
This dossier offers a critical reflection on the shame/pride dichotomy as an articulating axis of the LGBT world before and after the liberation movements of the 1970s. In the set of articles, the aim is to demonstrate that this dichotomy is in fact reductive since both everyday experiences and literary, audiovisual and film productions produced in Spain and Latin America throughout the twentieth and twenty-first centuries show that pride and shame are tensioned in a complex way: neither pride triumphs in an absolute way from the "liberation", nor shame is the paradigmatic experience of the previous period. The articles explore, in very diverse discourses –novels, newspapers, poetry, visual arts, documentaries, theatrical productions– how pride and shame constituted the subjectivities –and artistic manifestations– of dissident creators both in contexts that were mostly hostile to sex-gender diversity and in others that were progressively more tolerant.